Riboflavin Riboswitch Regulation: Hands-On Learning about the Role of RNA Structures in the Control of Gene Expression in Bacteria - Catherine E. Vrentas (American Society for Microbiology, 2018)
American Society for Microbiology (ASM) Curriculum Guidelines highlight the importance of instruction about informational flow in organisms, including regulation of gene expression. However, foundational central dogma concepts and more advanced gene regulatory mechanisms are challenging for undergraduate biology students. To increase student comprehension of these principles, we designed an activity for upper-level biology students centered on construction and analysis of physical models of bacterial riboswitches. Students manipulate an inexpensive bag of supplies (beads, pipe cleaners) to model two conformations of a riboswitch in a bacterial transcript. After initial pilot testing, we implemented the activity in three upper-level classes at one research-intensive and two primarily undergraduate institutions. To assess student perceptions of learning gains, we utilized a pre/post-activity 5-point Likert-type survey instrument to characterize student perceptions of confidence in both their understanding of riboswitches and their ability to apply the central dogma to riboswitches. Median post-test ranks were significantly higher than median pre-test ranks (p < 0.0001) when compared by the Wilcoxon signed-rank test (n = 31). Next, we assessed post-activity knowledge via use of a rubric to score student responses on exam questions. More than 80% of students could correctly describe and diagram examples of riboswitches; data from initial iterations were used to enhance curriculum materials for subsequent implementations. We conclude that this riboswitch activity leads to both student-reported increases in confidence in the ASM curriculum dimension of gene regulation, including central dogma concepts, and demonstrated student ability to diagram riboswitches, predict outcomes of riboswitches, and connect riboswitches to evolutionary roles.